Effect of chemical and magnetic seed treatments on growth, yield and seedling parameters of lentil (Lens esculenta L.) - Lokesh Kumar Prajapat; Prashant Kumar Rai; Rupesh Kumar; Kamlesh Sharma (Annals of Agricultural Research, 2022)
The field and laboratory experiments were conducted in the Department of Genetic and Plant Breeding SHUATS, Prayagraj, U.P. during 2018-19 to standardize the suitable method of chemical and magnetic seed treatment for lentil. Ten treatments of chemical and magnetic seed treatments were tested in Randomized Block Design (field experiment) and Completely Randomized Design (laboratory experiment) with three and four replications, respectively. Results revealed that the chemical seed treatment with treatment T4, Potassium di hydrogen phosphate (KH2 PO4 1%) recorded significantly fewer days to 50% flowering (72.3), significantly maximum plant height at 25 DAS (17.0) and 50 DAS (25.3 cm), highest number of primary branches/plant at 25 DAS (2.2) and 50 DAS (16.8), number of pods/plant (90.2), seed yield of (103.8 g/plot) and biological yield (236.8 g/plot) of lentil. Chemical seed treatment with T4 , Potassium di hydrogen phosphate (KH2 PO4 1%) also found effective in significant improvement in seedling parameters viz., germination percentage (96.2), root length (11.8), shoot length (9.9), seedling length (21.8), seedling vigour index I (2100), seedling vigour index II (472) and seedling dry weight (4.91 g) of lentil. The treatments T5 , Calcium chloride (CaCl2 1.5%) and magnetic treatment T9 (Magnetic treatment 150 mT (10 minutes) were also found effective in improving the above parameters of growth, yield and seedling of lentil.